Prevalence, socio-demographic features and risk factors of Hepatitis B virus infection among pregnant women in Southwestern Nigeria (2015)
Introduction: Hepatitis B virus is responsible for 50%-80% of Hepatocellular carcinoma cases worldwide. In Nigeria, vertical transmission remains a major route of Hepatitis B virus infection. Primary (vaccines and post-exposure prophylaxis) and secondary prevention of HBV transmission by appropriate sexual and sanitary practices are not yet optimal in the country yet measures for early detection (serological, molecular) and treatment of infected pregnant women is not a practice. This study aimed at identifying the prevalence and risk factors for Hepatitis B virus infection among pregnant women in Ibadan, Southwestern Nigeria. Methods: A cross-sectional study was done at the Ante-natal clinic of the University College Hospital Ibadan. One hundred and eighty pregnant women were recruited from March to August 2013, and tested for Hepatitis B surface antigen (BIORAD FRANCE) using third generation ELISA, as well as HIV-1 and 2 using Uni-Gold Recombigen and ALERE determine (a rapid immunoassay designed to detect antibodies to HIV 1 and/or 2). Positive HBsAg samples were tested for Hepatitis B envelope antigen, antibody and Hepatitis B core antibody (DIAPRO Italy) while serum HBV DNA was detected using PCR. Data were obtained using questionnaires to establish and analysis was performed using SPSS version 20. Results: The seroprevalence of HBsAg was 8.3% out of which 26.7% were positive for HBeAg, 53.3% had HBeAb, 20% had neither HBeAg nor HBeAb, 100% had total HBcAb and 86.7% had HBV DNA in their serum. The mean age was 32.1years, the highest HBV infection rate occurred in 25-29 year age group. Multiple sexual partners (OR- 3.987, P-value=0.026) and early age at sexual debut (OR 11.996, P- value=0.022) were independent risk factors for HBV infection. Conclusion: Hepatitis B virus infection is of high endemicity in Nigeria thus early detection, treatment of infected pregnant women, immunoprophylaxis for exposed newborns and surveillance for those with chronic infection is essential. Health education programs on prevention and control measures must be instituted.